Shaping Digital Ecosystems for Sustainable Production: Assessing the Policy Impact of the 2030 Vision for Industrie 4.0 - Björn Sautter (MDPI AG, 2021)
How can we effectively shape digital ecosystems for sustainable production in line with the Sustainable Development Goals of the United Nations? The German Plattform Industrie 4.0 has developed a vision for 2030 entitled “Shaping Digital Ecosystems Globally” with sustainability as one of three key pillars. Based on this vision, three development paths towards a digital, networked and sustainable manufacturing industry of the future were identified and further concretized with corresponding scenarios and business use cases. This article assesses this participatory approach of jointly thinking and shaping futures, with a particular focus on outcomes and policy impacts. A specific focus is placed on the involved and addressed public and private stakeholders, industry and policy sectors, and governance levels. The study shows that the 2030 Vision for Industrie 4.0 is a good example of how broad policy impacts can be achieved by taking a multi-actor, multi-sector and multi-level approach. Based on some practical implications for designing collaborative manufacturing networks in digital ecosystems, the article concludes with a call for collective action towards the Sustainable Development Goals to be achieved by the year 2030.